Further pitfalls in the diagnosis of mtDNA mutations: homoplasmic mt-tRNA mutations. Issue 1 (4th January 2008) - Tuppen, H A L; Fattori, F; Carrozzo, R; Zeviani, M; DiMauro, S; Seneca, S; Martindale, J E; Olpin, S E; Treacy, E P; McFarland, R; Santorelli, F M; Taylor, R W
Abstract : Background: Mitochondrial DNA (mtDNA) mutations are important causes of human genetic disease, with mutations in tRNA genes particularly prevalent. In many patients, mutations are heteroplasmic, affecting a population of mtDNA molecules. Establishing the pathogenicity of homoplasmic mitochondrial tRNA (mt-tRNA) mutations, in which the mutation is present in every mtDNA molecule, is extremely difficult. These mutations must conform to specific pathogenic criteria, documenting unequivocally a functional defect of the mutant mt-tRNA. Aims: To investigate the pathogenic nature of two homoplasmic mt-tRNA Thr deletions, m.15940delT (previously reported as pathogenic) and m.15937delA, by assessing the steady state levels of the mutant mt-tRNA in tissue and cell-line samples from six unrelated families, in which affected individuals were thoroughly investigated for mitochondrial DNA disease on the basis of clinical presentations. Rates of de novo mitochondrial protein synthesis were also examined in control and m.15937delA mutant fibroblasts. Results: Our data strongly suggest that both single nucleotide deletions are neutral polymorphisms; no obvious defects were apparent in either steady state mt-tRNA Thr levels or rates of mitochondrial protein synthesis. Conclusions: These findings have important implications for the investigation of other families with suspected mtDNA disease, in particular the requirement to fulfil strict and established pathogenic criteria in order to avoid misattribution of pathogenicity to mt-tRNA variants.